Divergent fortunes: growing wealth inequality and widening entrepreneurship by age. Issue 3 (3rd July 2019) - Weller, Christian E.; Wenger, Jeffrey B.
ABSTRACT: Entrepreneurship can offer people control over their working lives. Yet, it has declined among households younger than 50 years and grown among older households. We examine the relationship between growing wealth inequality and this widening entrepreneurial age disparities by focusing on wealth as a source of income diversification. Our main hypothesis is that younger households have less capital income from wealth holdings leading to less diversification as compared to older households. Using descriptive statistics and multinomial logistic regressions based on data from the Federal Reserve's triennial Survey of Consumer Finances (SCF), we conclude that the gap in households' entrepreneurial responsiveness to income diversification has widened by age. We also find that households' capital income receipt follows from wealth such that rising wealth inequality may have impeded income diversification and reduced entrepreneurship among households with less wealth, especially younger ones. We rule out three alternative explanations: increasing economic pressures from labor market instability, tightening of liquidity constraints, and in declines in nonpecuniary rewards – for the divergent entrepreneurship trends.